Insight into the Transition‐Metal Hydroxide Cover Layer for Enhancing Photoelectrochemical Water Oxidation. (15th December 2020) - Ning, Xingming; Du, Peiyao; Han, Zhengang; Chen, Jing; Lu, Xiaoquan
Abstract: Depositing a transition‐metal hydroxide (TMH) layer on a photoanode has been demonstrated to enhance photoelectrochemical (PEC) water oxidation. However, the controversial understanding for the improvement origin remains a key challenge to unlock the PEC performance. Herein, by taking BiVO4 /iron‐nickel hydroxide (BVO/F x N4− x ‐H) as a prototype, we decoupled the PEC process into two processes including charge transfer and surface catalytic reaction. The kinetic information at the BVO/F x N4− x ‐H and F x N4− x ‐H/electrolyte interfaces was systematically evaluated by employing scanning photoelectrochemical microscopy (SPECM), intensity modulated photocurrent spectroscopy (IMPS) and oxygen evolution reaction (OER) model. It was found that F x N4− x ‐H acts as a charge transporter rather than a sole electrocatalyst. PEC performance improvement is mainly ascribed to the efficient suppression of charge recombination by fast hole transfer kinetics at BVO/F x N4− x ‐H interface. Abstract : By taking BVO/F x N4− x ‐H as a model, we directly track the behavior of hole transfer. Through a system dynamics analysis of the key charge transfer and surface catalytic reaction at the different interfaces, we clarify that F x N4− x ‐H here acts as an interfacial charge transporter. PEC performance is mainly enhanced by efficiently suppressing BVO/F x N4− x ‐H interface charge recombination.